Managing Polarities in Congregations: Eight Keys for Thriving Faith Communities - Oswald, Roy M.; Johnson, Barry (Rowman & Littlefield Publishers, 2009)
Congregations often find themselves in power struggles over two opposing views. People on both sides believe strongly that they are right. They also assume that if they are right, their opposition must be wrong--classic 'either/or' thinking. A polarity is a pair of truths that need each other over time. When an argument is about two poles of a polarity, both sides are right and need each other to experience the whole truth. This phenomenon has been recognized and written about for centuries in philosophy and religion. It is at the heart of Taoism, where we find the familiar polarity of yin and yang energy. In the past fifty years, business leaders have come to appreciate the phenomenon, often called dilemma or paradox. No matter what it is called, the research is clear: leaders and organizations that manage polarities well outperform those who don't.